Knee- and Ankle-Joint Torques Contribute to Controlling the Whole-Body Linear and Angular Momenta in the Single-Support Phase after Tripping during Gait - Nakajima, Takahiro; Fukashiro, Senshi; Yoshioka, Shinsuke (International Journal of Sport and Health Science, 2023)
This study aims to investigate the kinetic mechanisms of controlling the whole-body linear momentum (WBLM) and whole-body angular momentum around the whole-body center of mass (WBAM) in the single-support phase after tripping during gait. Twelve young participants were made to trip during gait, and the kinematics and kinetics of their recovery responses were recorded using a 17-camera motion capture system and force platform. We found that the knee-flexion torque of the support leg dominantly contributed to the decrease in the forward WBAM increased owing to tripping, whereas this torque caused a significant forward WBLM at foot landing. The ankle-plantarflexion torque of the support leg contributed to the prevention of the body descent in the first half of this phase, although this effect decreased in the later phase, resulting in the increase in the downward WBLM at foot landing. The ankle-plantarflexion torque also contributed to the increase in the forward WBLM at foot landing. These results indicate that the ankle- and knee-joint torque exertions of the support leg are the main contributors to the change in WBLM and WBAM in the single-support phase after tripping during gait. This study also suggests that there is a trade-off relationship between the control of WBLM and WBAM, and younger adults prioritize the WBAM adjustment during this phase.